2020
DOI: 10.3390/biom10020302
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Thiosulfate in the Pregnant Dahl Salt-Sensitive Rat, a Model of Preeclampsia

Abstract: Aberrant production of hydrogen sulfide (H2S) has been linked to preeclampsia. We hypothesized that sodium thiosulfate (STS), a H2S donor, reduces hypertension and proteinuria, and diminishes fetal growth restriction in the Dahl salt-sensitive (S) rat, a spontaneous model of superimposed preeclampsia. In addition to a control group (n = 13), two groups received STS via drinking water at a dose of 2 g (n = 9) or 3 g per kg body weight per day (n = 8) from gestational day (GD) 10 to 20. Uterine artery resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Dahl salt‐sensitive rats (DSSR) are a genetic model of salt‐induced hypertension, renal injury, and insulin resistance (Rapp, 1982). Recent studies have reported the preeclamptic phenotype and fetal growth restriction in DSSR, which replicate many characteristics of preeclampsia in humans (Dasinger et al, 2020; Gillis et al, 2015; Terstappen et al, 2019, 2020; Turbeville et al, 2019). During pregnancy, DSSR spontaneously display increased blood pressure, proteinuria and placental hypoxia and reduced uteroplacental blood flow.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Dahl salt‐sensitive rats (DSSR) are a genetic model of salt‐induced hypertension, renal injury, and insulin resistance (Rapp, 1982). Recent studies have reported the preeclamptic phenotype and fetal growth restriction in DSSR, which replicate many characteristics of preeclampsia in humans (Dasinger et al, 2020; Gillis et al, 2015; Terstappen et al, 2019, 2020; Turbeville et al, 2019). During pregnancy, DSSR spontaneously display increased blood pressure, proteinuria and placental hypoxia and reduced uteroplacental blood flow.…”
Section: Introductionmentioning
confidence: 70%
“…preeclampsia in humans (Dasinger et al, 2020;Gillis et al, 2015;Terstappen et al, 2019Terstappen et al, , 2020Turbeville et al, 2019). During pregnancy, DSSR spontaneously display increased blood pressure, proteinuria and placental hypoxia and reduced uteroplacental blood flow.…”
Section: What Is the Clinical Significancementioning
confidence: 99%
“…Dahl sat sensitive rats (DSSR) is a genetic model of salt-induced hypertension, renal injury and insulin resistance 22 . Recent studies have reported the preeclamptic phenotype and fetal growth restriction in DSSR, which reminisce many characteristics of preeclampsia in human [23][24][25][26][27] . During pregnancy, DSSR spontaneously displays increased blood pressure, proteinuria, placental hypoxia and reduced uteroplacental blood flow.…”
Section: Introductionmentioning
confidence: 85%
“…Although inorganic sulfide salts (NaHS and Na 2 S) have been the most widely employed in biological and preclinical studies, none of them are unlikely to be a suitable clinical option for a number of reasons, including poor water solubility, fast and uncontrollable release, and unpleasant odor. Given that it is not trivial to synthesize a clinically suitable H 2 S donor in a short time, three types of potential H 2 S donors or drugs should be considered to block viral entry: (1) natural H 2 S donors (e.g., garlic and onions) [ 127 , 128 ] or dietary micronutrients (e.g., L-cysteine and taurine) [ 129 , 130 ], (2) H 2 S-donating derivatives of clinically used drugs that link various H 2 S donating groups to clinically used drugs (e.g., ATB-346 [ 131 ] and GIC-1001 [ 132 ] which has completed phase 2 clinical trial), and (3) several clinically used drugs that have been verified to increase H 2 S levels (e.g., α -lipoic acid, [ 133 ] sodium thiosulfate, [ 134 ] zofenoprilat, [ 135 ] and N-acetylcysteine [ 136 ]). Sodium thiosulfate has been proposed as an inhalation therapy for COVID-19, [ 137 ] and it was confirmed that the combined application of N-acetylcysteine improved the symptoms in COVID-19 patient.…”
Section: Discussionmentioning
confidence: 99%